ISOLATION AND CHARACTERISTICS OF BOVINE SKIN GELATIN AND ANALYSIS OF GLYCINE, PROLINE, AND HYDROXYPROLINE BY HIGH-PERFORMANCE LIQUID CHROMATOGRAPHYFLUORESCENCE - Khoirunnisa, Dini; ., Harmita; Rukmana, Taufiq Indra (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to isolate gelatin, determine its characteristics, and obtain analytical methods optimum for the determination of glycine, proline, and hydroxyproline levels in bovine gelatin. Methods: Bovine hide was hydrolyzed using 2% sodium hydroxide at an extraction temperature of 70°C for 3 h and a drying temperature of 60°C. Then, the gelatin extracts were evaluated using an organoleptic test; Fourier transform infrared analysis; pH measurement; and ash content, moisture content, and viscosity tests. Optimum analysis conditions for the determination of glycine, proline, and hydroxyproline levels in bovine gelatin using high-performance liquid chromatography with a fluorescence detector were as follows: Excitation wavelength, 265 nm; emission wavelength, 320 nm; mobile phase composition of acetic buffer: acetonitrile, 55:45; flow rate, 0.8 mL/min; C18 column with length 250 mm and inner diameter 4.6 mm; and particle size, 5 μm. Derivatization of amino acids was performed using the reagent 9-fluorenylmethoxycarbonyl chloride. Results: The results showed average levels of glycine, proline, and hydroxyproline in bovine gelatin, i.e., 25.10±0.09%, 14.28±0.11%, and 13.0±0.05%, respectively. Conclusion: The optimum conditions for bovine gelatin hydrolysis included HCl with heating for 22 h at 110°C. The hydroxyproline, glycine, and proline levels obtained for analysis in bovine gelatin samples were 13.50±0.05%, 25.11±0.09%, and 14.28±0.11%, respectively.